Cultivo do rambotä - Sacramento, Célio Kersul Do; Andrade, Renata Aparecida [UNESP] (Sociedade Brasileira de Fruticultura, 2014)
The cultivation of rambutan (Nephelium lappaceum L.) is a recent activity in Brazil and many of the technical recommendations are extrapolated from other producing countries. In Brazil, the commercial plantation of rambutan, are restricted to the states of Bahia, Pará and Säo Paulo and are formed by plants propagated sexually, and so presents a high genetic variability. This variability rambuteiras has allowed the selection of genotypes that produce fruit with the features required for export. Some pests and diseases have been reported in rambuteiras in Brazil. The production is sold domestically as fresh fruit.

O cultivo da rambuteira (Nephelium lappaceum L.) é uma atividade recente no Brasil, e muitas das recomendações técnicas säo extrapoladas de outros países produtores. No Brasil, os plantios comerciais de rambotä estäo restritos aos Estados da Bahia, Pará e Säo Paulo, e säo formados por mudas propagadas sexuadamente, apresentando, portanto, grande variabilidade genética. Essa variabilidade de rambuteiras tem permitido a seleção de genótipos que produzem frutos com as características requeridas para exportação. Algumas pragas e doenças têm sido relatadas em rambuteiras no Brasil. A produção é comercializada no mercado interno, na forma de frutos in natura.
Farming rambutan
Keywords: production; quality; propagation; produção; qualidade; propagação